Mitochondrial Genome Architecture and Evolutionary Origin of the Yao Silkworm, a Living Fossil of the Domestic Silkworm Bombyx mori (Lepidoptera: Bombycidae). Issue 2 (18th March 2022) - Zhang, Gui-Zheng; Zhang, Yu-Li; Wei, Wei; Li, Yu-Ping; Liu, Yan-Qun; Bi, Li-Hui; Lu, Cheng
Abstract: The Yao silkworm is a unique silkworm resource producing yellow flat plate silk that has only been reared by the Baiku Yao ethnic group in Nandan County, Guangxi Province, China for a thousand years. Here, we report the mitochondrial genomes (mitogenomes) of five Yao silkworm strains and 10 local Guangxi strains of the domestic silkworm ( Bombyx mori ) L. (Lepidoptera: Bombycidae), and use the resulting mitogenomes and the available Bombyx mitogenomes to characterize their genome architecture and trace the evolutionary origin of the Yao silkworm. The five Yao silkworm mitogenomes exhibited genome architectures identical to typical set of 37 mitochondrial genes (13 protein-coding genes, 22 transfer RNAs, and two ribosomal RNAs) and a high level of genome sequence similarity with the domestic silkworm. Mitogenome-based phylogenetic reconstruction provided solid evidence that the Yao silkworm shares a common ancestor with the domestic silkworm. Sliding window analysis uncovered a distinct variation pattern in the mitogenome between the Yao silkworm and the other domestic silkworm strains. The phylogenetic analyses revealed a basal placement of the Yao silkworm among all available domestic silkworm strains, indicating that the Yao silkworm is an ancient population of the domestic silkworm. Our data indicated that the Yao silkworm ( B. mori ) is a lineage of the domestic silkworm, which for the first time provides insights into the origin of the Yao silkworm.